Challenges and progress in the implementation of Education for Peace in Latin America - Pérez Fuentes, Carlos Alfredo; Alvarez Maestre, Annie Julieth (Revista Colombiana de Ciencias Sociales, 2021)
This article is the result of a research project financed by COLCIENCIAS in 2018, named "Paz App as a democratic tool for the normative implementation of Peace Cathedra based on social imaginary, conceived in eleventh grade students in public educational institutions". The goal of this article is to analyze the cases where education for peace was implemented in Latin America, which also seeks to call attention of the competent authorities and the community itself in order to address the reassessment of educational models in order to have their curricular independence or transversality adapt better to the needs of every State. All of this keeping in mind the methodological criteria that are useful in the development of an education towards peace given by cases of its implementation all over the world. In this way, the methodology used in this research is based on a qualitative approach that under a bibliographic design allowed the exhaustive document review needed for its eventual analysis, using the discourse analysis that allows to relate the independent education towards peace categories as an integrated whole in the exercise of interpretation and understanding of the literature that was the object of this study. As a result of this research, it is shown how big efforts have been done to accomplish the implementation of the education towards peace in the Latin American contexts from the fundamental theories of peace.